Axial bearing capacity of large-diameter grouted connections analyzed by means of a simplified double shear test. (1st March 2017) - Wang, Zhenyu; Zhang, Yi; Chen, Feng; Wang, Guoqing; Wang, Lizhong; Jiang, Jianqun
Highlights: The study of the relationship between grouted connections and plate specimens. Investigation of shear-slippage curves and cracking in high-strength grout. Numerical simulation used to verify test results using the Brittle Cracking Model. Application of double shear test as a simple method of studying grouted connections. Abstract: Grouted connections have recently been widely used in the support structures of offshore wind turbines. As these connections are strong and large, full-scale testing has been proved difficult. Double shear specimens with a high strength grout-to-steel plate interface have been tested with shear keys to investigate the characteristics of crack propagation, shear-slippage and bearing mechanism. In this paper, the Brittle Cracking Model is applied to simulate the double shear testing and axial compression of large-diameter grouted connections. The finite element (FE) model is an efficient means of simulating cracking-pattern and the shear-slippage process of grout. The numerical simulations are verified against the test results and DNV code results. The results show that the shear capacity of large-diameter grouted connections can be calculated by using a double shear test based on the relationship between the stiffness of the grouted connections and the double shear specimen. The accuracy of the simplified formula is verified by using experimental shear stress data against numerical simulation and DNV code results. The double shear test is thus proved to be a simple and accurate method of studying the shear capacity of large-diameter grouted connections.